A method for preparing high thermal conductivity phase change heat storage material using organic pollutant waste salt

Through the mixed sintering process of industrial waste salt and gold tailings, high-thermal phase change heat storage materials are prepared, which solves the problems of organic pollutant disposal and phase change material leakage in industrial waste salt, and achieves the improvement of material thermal conductivity and efficient utilization of solid waste.

CN115948151BActive Publication Date: 2025-05-02NEW MATERIAL INST OF SHANDONG ACADEMY OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310092696.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-06
Publication Date
2025-05-02
Estimated Expiration
2043-02-06

AI Technical Summary

Technical Problem

Organic pollutants in industrial waste salt are difficult to dispose of, phase change materials are prone to leak during sintering, have low thermal conductivity, and the overall utilization rate of solid waste is low.

Method used

High thermal phase change heat storage materials are prepared by mixed sintering process using industrial waste salt and gold tailings. Organic pollutants in industrial waste salts are carbonized by high temperature burning to form carbon black, which improves thermal conductivity; gold tailings are used as auxiliary packaging materials to prevent the leakage of molten salt through capillary force and surface tension.

Benefits of technology

The harmless disposal of industrial waste salt has been achieved, the thermal conductivity of phase-change heat storage materials has been improved, the heat storage density and mechanical strength of the materials have been enhanced, and the application and utilization efficiency of industrial solid waste have been expanded.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115948151B_ABST
    Figure CN115948151B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of phase change heat storage materials, and relates to a preparation method of a high thermal conductivity phase change heat storage material using organic pollutant waste salt, comprising: crushing industrial waste salt and gold tailings, heating and dehydrating, and standing by; mixing the dehydrated gold tailings and industrial waste salt evenly, ball milling, and obtaining a mixed powder; transferring the mixed powder to a rigid mold and pressing to obtain a green body; sintering the green body under a nitrogen atmosphere, and cooling to room temperature. Organic pollutants in industrial waste salts are burned at high temperatures to form carbon black, which can completely decompose the organic pollutants and achieve harmless disposal of industrial waste salts; on the other hand, the carbon black produced by carbonization can improve the thermal conductivity of phase change heat storage materials. Selecting gold tailings as packaging materials can give full play to the pore structure of natural raw materials, and obtain a shaped phase change heat storage material with controllable adsorption capacity and stable adsorption performance, which broadens the application field and utilization efficiency of industrial solid waste.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of phase change heat storage materials, and in particular relates to a method for preparing a high thermal conductivity phase change heat storage material by utilizing organic pollutant waste salt. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Industrial waste salt mainly comes from the production process of pesticides, medicines, fine chemicals, petrochemicals and other industries. The main components are inorganic salts, including chlorides, sulfates, nitrates, etc. These waste salts usually contain organic pollutants and other toxic components and are listed as hazardous wastes. Pesticide production is the main industry that produces waste salt. The production of 1 ton of pesticide products produces an average of about 1 ton of waste salt, which mainly comes from the production process of pesticide intermediates and original drugs. Therefore, the annual production of pesticide waste salt can reach more than 1 million tons. Industrial waste salt has the characteristics of a wide variety, large production volume, complex composition, high toxicity, high processing cost, and great environmental harm. It is difficult to recycle resources. At present, the usual disposal method is incineration or landfill, and the processing cost is as high as 2,500-4,000 yuan / ton, and it has potential pollution risks to soil, water, etc. In recent years, people's awareness of resource conservation and environmental friendliness has gradually increased, and the treatment and resource utilization of waste salt in chemical production has received increasing attention. The harmless disposal, recycling and reuse of industrial waste salt can not only eliminate harm to the environment, but also achieve the recycling of resources.

[0004] Molten salt, as a commonly used solid-liquid high-temperature phase change energy storage material, has the advantages of high heat storage density, high boiling point, low viscosity, low vapor pressure and high volume heat. It is an excellent heat transfer and heat storage medium that can store and release heat energy through solid-liquid phase transition. It has broad market prospects and economic benefits in the efficient use of solar energy, the use of industrial waste heat, and cross-seasonal heat storage and heating. Since the main components of industrial waste salt are inorganic salts such as chlorides and sulfates, it has the potential to be used as a phase change heat storage molten salt for resource utilization. However, in the actual application process, molten salt phase change energy storage materials have the problems of easy leakage during operation and low heat transfer efficiency (low thermal conductivity). In order to solve the problem of easy leakage of phase change heat storage materials during operation, porous support materials such as porous ceramics, diatomaceous earth, expanded perlite, expanded graphite, etc. are used as carriers to provide shape stability through capillary force and surface tension, which can limit the leakage of liquid molten salt in the structure. However, there is currently no packaging material suitable for industrial waste salt. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a method for preparing a high thermal conductivity phase change heat storage material based on organic pollutant waste salt. Industrial waste salt is classified as hazardous waste, but the existing methods for treating industrial waste salt are mainly incineration and landfill, which have high disposal costs and are prone to secondary pollution risks. The present invention solves the problems in the related art that organic pollutants in industrial waste salt are difficult to dispose of, phase change materials are prone to leakage during sintering, thermal conductivity is low, and overall utilization rate of solid waste is low. Industrial waste salt containing organic pollutants is selected as the molten salt medium in the phase change energy storage material, and the industrial solid waste of gold tailings is used as an auxiliary packaging raw material. Through a mixed sintering process, a method for preparing an industrial waste salt-gold tailings high thermal conductivity phase change heat storage material is obtained. The organic pollutants in the industrial waste salt are carbonized to form carbon black through high-temperature burning. On the one hand, the organic pollutants can be completely decomposed to achieve harmless disposal of industrial waste salt; on the other hand, the carbon black produced by carbonization can improve the thermal conductivity of the phase change heat storage material. Selecting gold tailings as packaging materials can give full play to the pore structure of natural raw materials. Through capillary force and surface tension, a shaped phase change heat storage material with controllable adsorption capacity and stable adsorption performance is obtained, which expands the application field and utilization efficiency of industrial solid waste.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] The first aspect of the present invention provides a method for preparing a high thermal conductivity phase change heat storage material using organic pollutant waste salt, comprising:

[0008] The industrial waste salt and gold tailings are crushed, heated and dehydrated for later use;

[0009] The dehydrated gold tailings and industrial waste salt are mixed evenly in a mass ratio of 1:0.8-1.5, and ball-milled to obtain a mixed powder;

[0010] Transferring the mixed powder into a rigid mold and pressing to obtain a green body;

[0011] The green body is sintered in a nitrogen atmosphere and cooled to room temperature to obtain a green body.

[0012] The study found that compared with other porous supporting materials, such as porous ceramics, diatomaceous earth, expanded perlite, and expanded graphite, the packaging technology of aluminum-silicon industrial solid waste such as gold tailings for phase change heat storage materials is not only expected to provide a cheap, widely available, and large-reserved packaging material to reduce the overall cost of the thermal energy storage system, but also can turn waste into treasure, improve the utilization rate of silicon-aluminum solid waste and its added value, effectively alleviate the situation of difficult disposal of solid waste storage, and reduce environmental pollution. The main preparation method is the mixed sintering method, which mixes, presses, and sinters gold tailings and industrial waste salt to prepare a shaped phase change heat storage material, which is an effective method to effectively realize the industrial batch packaging of phase change heat storage materials.

[0013] At the same time, organic impurities in industrial waste salt are carbonized through high-temperature burning. On the one hand, organic pollutants in industrial waste salt are removed, and on the other hand, the carbon black produced can further improve the heat transfer efficiency of the shaped phase change heat storage material, achieving the purpose of killing two birds with one stone.

[0014] The second aspect of the present invention provides a high thermal conductivity phase change heat storage material prepared by the above method.

[0015] The third aspect of the present invention provides the application of the above-mentioned high thermal conductivity phase change heat storage material in the field of solid waste utilization and heat storage.

[0016] Beneficial effects of the present invention

[0017] (1) The method for treating industrial waste salt provided by the present invention completely carbonizes the organic pollutants in the industrial waste salt to form carbon black through medium-high temperature sintering under anaerobic conditions, so that the industrial waste salt can maintain a high temperature state for a long time, effectively treating and purifying the waste salt, and the generated carbon black improves the thermal conductivity of the waste salt, thereby promoting the energy storage efficiency. Preferably, adding a certain mass ratio of flake graphite to the industrial waste salt can further improve the thermal conductivity of the waste salt. The present invention realizes the resource utilization of waste salt containing organic pollutants and phase change heat storage materials. Through medium-high temperature sintering treatment and purification, high thermal conductivity molten salt is obtained, which is used to shape composite phase change heat storage materials, and unstable heat sources generated by industrial waste heat, solar energy, etc. are directly converted into thermal energy in a discontinuous or continuous form and stored in phase change heat storage materials. While realizing the resource utilization of industrial waste salt, its thermal conductivity efficiency is improved, which is of great significance for improving the energy conversion efficiency in practical applications;

[0018] (2) The selected industrial solid waste gold tailings are considered to be a good choice for the molten salt phase change material carrier. Gold tailings have a high porosity and a large specific surface area, which can provide a large number of attachment sites for the molten salt, and can effectively prevent leakage during the molten salt phase change process by virtue of its capillary force and surface tension. The carrier material has the advantages of high temperature resistance, high strength, and high porosity. When the temperature is higher than the melting point of the phase change material, the composite material can not only maintain its original shape and have a certain mechanical strength, but also has a higher energy storage density. The present invention broadens the application field of gold tailings and improves its resource utilization efficiency;

[0019] (3) The preparation method of the high thermal conductivity fixed-shape phase change heat storage material of the present invention is simple in process, and adopts a pressing-sintering process to mix and sinter industrial waste salt and gold tailings to prevent the phase change material from leaking out at high temperature; the phase change heat storage material has high strength, high heat storage density, good fixing effect and is not easy to leak. The material compressive strength reaches more than 23MPa, the phase change energy storage effect is good, the phase change temperature is 300-500℃, and the heat storage density is 444.86J·g -1The thermal conductivity is 3-5 times higher than that of industrial waste salt, reaching 2.0-3.2W (m·K) -1 .

[0020] (4) The preparation method of the present invention is simple, practical and easy to promote. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention, and the exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute improper limitations on the present invention.

[0022] Figure 1 The particle size distribution diagram of gold tailings is selected for the present invention;

[0023] Figure 2 A flow chart of industrial waste salt treatment and phase change heat storage material preparation of the present invention;

[0024] Figure 3 This is a microstructure diagram of the phase change heat storage material in the present invention. DETAILED DESCRIPTION

[0025] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0026] A method for preparing a high thermal conductivity phase change heat storage material using organic pollutant waste salt, comprising:

[0027] Industrial waste salt and gold tailings are used together to prepare high thermal conductivity phase change heat storage materials. The molten salt component in the industrial waste salt can be used as the heat storage medium, and the gold tailings can be used as a carrier to prevent the leakage of molten salt during the phase change process. At the same time, the organic matter in the industrial waste salt is carbonized to form carbon black under high-temperature sintering, which can further improve the thermal conductivity of the phase change heat storage material and accelerate the storage and release efficiency of thermal energy, providing a resource-based utilization method for the disposal of industrial waste salt and gold tailings.

[0028] The main components of the selected gold tailings are SiO2, Al2O3 and other oxides. The proportions of each component are shown in Table 1. Figure 1 The particle size analysis diagram of the selected gold tailings is shown below. Figure 1 It can be seen that more than 50% of the particles have a size less than 22.3 μm.

[0029] Table 1 Composition analysis of selected gold tailings

[0030]

[0031] Step 1: Use a spiral crusher to crush industrial waste salt and gold tailings, and randomly select some samples for XRF quantitative analysis to obtain the proportion of each chemical component in the solid waste particles;

[0032] Step 2: Heat the industrial waste salt and gold tailings to 120°C and keep it warm for 6 hours to remove the moisture adsorbed in the structure;

[0033] Step 3: weigh the gold tailings and industrial waste salt raw materials according to the required mass ratio of 1: (0.8-1.5), place them in a ball mill to mix them to obtain a mixed powder, and then transfer the mixed powder to a rigid mold and press them to obtain a green body;

[0034] Step 4: Sinter the pressed green body in a muffle furnace under nitrogen atmosphere for 3 hours, and finally cool to room temperature to obtain the industrial waste salt / gold tailings high thermal conductivity phase change heat storage material.

[0035] In the present invention, as a preferred technical solution, in step 1, 5% by mass of flake graphite is added to industrial waste salt, and mixed evenly to obtain a thermally conductive enhanced composite molten salt;

[0036] In the present invention, as a preferred technical solution, in step 3, the gold tailings and industrial waste salt are mixed in a ball mill at a speed of 200 r / min for 2 hours to obtain a mixed powder;

[0037] In the present invention, as a preferred technical solution, in step three, the mixed powder is pressed in a rigid mold using a uniaxial press with the pressure increased to 40 MPa and the pressure is maintained for 120 seconds.

[0038] In the present invention, as a preferred technical solution, in step 4, the sintering temperature is 450-550°C.

[0039] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.

[0040] In the following examples, the main components of the gold tailings used are SiO2, Al2O3 and other oxides, and the proportions of each component are shown in Table 1. Figure 1 The particle size analysis diagram of the selected gold tailings is shown below. Figure 1 It can be seen that more than 50% of the particles have a size less than 22.3 μm.

[0041] Table 1 Composition analysis of selected gold tailings

[0042]

[0043] In the following examples, industrial waste salts all come from a chemical enterprise in Binzhou, Shandong.

[0044] Example 1

[0045] like Figure 2 As shown, a method for preparing a high thermal conductivity shaped phase change heat storage material of industrial waste salt-gold tailings, the steps are as follows:

[0046] (1) Using a spiral crusher to crush industrial waste salt and gold tailings, and randomly taking some samples for XRF quantitative analysis to obtain the proportion of each chemical component in the solid waste particles;

[0047] (2) heating industrial waste salt and gold tailings to 120°C and keeping the temperature for 6 hours;

[0048] (3) The gold tailings and industrial waste salt obtained in (2) are weighed according to the required mass ratio of 1:1.2, mixed in a ball mill at a speed of 200 r / min for 5 h to obtain a mixed powder, and then the mixed powder is transferred to a primary pressing rigid mold for pressing to obtain a green body, and the pressing conditions are: using a uniaxial press to increase the pressure to 40 MPa and maintain the pressure for 120 s;

[0049] (4) The pressed green body is sintered in a muffle furnace at 500°C under a nitrogen atmosphere for 3 h, and finally cooled to room temperature to obtain the finished product.

[0050] (5) The high thermal conductivity phase change heat storage material prepared in this example has a compressive strength of 23.62 MPa and a heat storage density of 460 J·g -1 , thermal conductivity reaches 1.02W(m·K) -1 , compared with industrial waste salt (thermal conductivity 0.69W (m·K) -1 ) increased by 1.48 times.

[0051] Example 2

[0052] like Figure 2 As shown, a method for preparing a high thermal conductivity shaped phase change heat storage material of industrial waste salt-gold tailings, the steps are as follows:

[0053] (1) Using a spiral crusher to crush industrial waste salt and gold tailings, and randomly taking some samples for XRF quantitative analysis to obtain the proportion of each chemical component in the solid waste particles;

[0054] (2) adding 5% by mass of flake graphite to industrial waste salt;

[0055] (3) heating the industrial waste salt and gold tailings to 120° C. and keeping the temperature for 6 hours;

[0056] (4) The gold tailings and industrial waste salt obtained in (3) are weighed according to the required mass ratio of 1:1.4, mixed in a ball mill at a speed of 200 r / min for 5 h to obtain a mixed powder, and then the mixed powder is transferred to a primary pressing rigid mold for pressing to obtain a green body. The pressing conditions are: using a uniaxial press to increase the pressure to 40 MPa and maintain the pressure for 120 s;

[0057] (4) The pressed green body is sintered in a muffle furnace at 500°C under a nitrogen atmosphere for 3 h, and finally cooled to room temperature to obtain the finished product.

[0058] (5) The high thermal conductivity phase change heat storage material prepared in this example has a compressive strength of 25.27 MPa and a heat storage density of 483 J·g -1 , thermal conductivity reaches 2.62W(m·K) -1 , compared with industrial waste salt (thermal conductivity 0.69W (m·K) -1 ) increased by 3.80 times.

[0059] Comparative Example 1

[0060] The difference from Example 1 is that diatomite is used instead of gold tailings, the particle size range is 100-150 μm, the compressive strength is 15.84 MPa, and the heat storage density is 415.2 J·g -1 , thermal conductivity is 0.97W(m·K) -1 .

[0061] Comparative Example 2

[0062] The difference from Example 1 is that expanded perlite is used instead of gold tailings, with a particle size range of 180-330 μm, a compressive strength of 12.15 MPa, and a heat storage density of 387.8 J·g -1 , thermal conductivity is 0.89W(m·K) -1 .

[0063] Comparative Example 3

[0064] The difference from Example 2 is that expanded graphite is used instead of flake graphite, with a compressive strength of 24.15 MPa and a heat storage density of 480 J·g -1 , thermal conductivity reaches 2.37W(m·K) -1 However, compared with flake graphite, the cost of using expanded graphite is 5-7 times higher.

[0065] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may be modified and varied in various ways. Within the spirit and principle of the present invention,

[0066] Any modifications, equivalent substitutions, improvements, etc. made should be included in the protection scope of the present invention.

Claims

1. A method for preparing a high thermal conductivity phase change heat storage material using organic pollutant waste salt, characterized in that: include: The industrial waste salt and gold tailings are crushed, heated and dehydrated respectively for later use; The industrial waste salts are inorganic salts, including chlorides, sulfates, and nitrates; The specific conditions of the heating dehydration are heating to 120-130°C and keeping warm for 5-6 hours; The dehydrated gold tailings and industrial waste salt are mixed evenly in a mass ratio of 1:0.8-1.5, and ball-milled to obtain a mixed powder; Transferring the mixed powder into a rigid mold and pressing to obtain a green body; The green body is sintered in a nitrogen atmosphere and cooled to room temperature to obtain; The sintering condition is sintering at 450-550° C. for 3-4 hours.

2. The method for preparing a high thermal conductivity phase change heat storage material using organic pollutant waste salt as claimed in claim 1, characterized in that: Add 5-6% by mass of flake graphite to industrial waste salt, mix them evenly, and obtain a thermally conductive enhanced composite molten salt.

3. The method for preparing a high thermal conductivity phase change heat storage material using organic pollutant waste salt according to claim 1, characterized in that: The rotation speed of the ball mill is 200-240 r / min, and the mixing time is 1.5-2 h.

4. The method for preparing a high thermal conductivity phase change heat storage material using organic pollutant waste salt according to claim 1, characterized in that: The specific conditions of the pressing are: increasing the pressure to 40-45 MPa and maintaining the pressure for 120-130 seconds.

5. A high thermal conductivity phase change heat storage material prepared by the method according to any one of claims 1 to 4.

6. Application of the high thermal conductivity phase change heat storage material according to claim 5 in the field of solid waste utilization and heat storage.

Citation Information

Patent Citations

  • Waste dreg composite phase-change material non-fired light aggregate and preparation method thereof

    CN108373279A

  • Impurity salt heat storage material and preparation method thereof

    CN114181673A